2023
DOI: 10.1039/d2nj04135a
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-based dot-capped gold nanoparticles hybridized with manganese dioxide for enhanced photodynamic cancer therapy

Abstract: Carbon based dots capped gold nanoparticles (AuNPs/CDs) are synthesized and found to present high singlet oxygen (1O2)-generation capability due to the synergistic effect of the strong localized surface plasmon resonance...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…For instance, the application of gold-based nanoparticles as theranostics is shown in Figure 1 [38]. Surveys such as that conducted by Hu et al [39] have shown that carbon-based, dot-capped gold nanoparticles (AuNPs/CDs) are promising photosensitizers for photodynamic therapy applications. The most striking result to emerge from the literature reviews in gold-based NPs is that the gold-based NPs, due to their special features, are good clinical candidates for use in cancer detection and treatment.…”
Section: Gold-based Nanoparticlesmentioning
confidence: 99%
“…For instance, the application of gold-based nanoparticles as theranostics is shown in Figure 1 [38]. Surveys such as that conducted by Hu et al [39] have shown that carbon-based, dot-capped gold nanoparticles (AuNPs/CDs) are promising photosensitizers for photodynamic therapy applications. The most striking result to emerge from the literature reviews in gold-based NPs is that the gold-based NPs, due to their special features, are good clinical candidates for use in cancer detection and treatment.…”
Section: Gold-based Nanoparticlesmentioning
confidence: 99%